Immune response to Aspergillus fumigatus in compromised hosts: from bedside to bench. (January 2011) - Chai, Louis YA; Vonk, Alieke G; Kullberg, Bart-Jan; Netea, Mihai G
The relevance of studies aimed at understanding host immune response against Aspergillus fumigatus takes on much significance given that all patients with invasive aspergillosis are invariably immunocompromised. This article attempts to correlate relevant findings from recent experimental studies to clinical observations made by the physician at the bedside. It is hoped that the increased understanding of host–fungus immune interaction may pave the way for the development of new management strategies against this difficult-to-treat fungal disease.